Optimasi Daerah Irigasi Muara Jalai Kecamatan Kampar Utara Kabupaten Kampar Provinsi Riau - Hafid Muhaimin Hasward; Manyuk Fauzi; Siswanto Siswanto (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Rice field area in Riau Province in the last 10 years experienced a rate decrease each year from 2004 to 2013 amounted to 7.23%. For irrigated areas Muara Jalai occurrence over the land like a wetland conversion to oil palm and mining quary that reduce water catchment areas. In previous studies the overall use of water in irrigated areas Muara Jalai otherwise not optimal, which is not optimal rate is 47.3% (<50%) by using analysis of analytical hierarchy process (AHP). For this study focused on a review of optimization in irrigated areas Muara Jalai in order to obtain optimal results related to water availability. The method used in this study as a method mock and modified Penman method. While the application used in this study CropWat, ArcGIS, Auto Cad, and Microsoft Excel. The results of climatological data input using the application CropWat gained 3.38 mm/day. Irrigation Area watershed area in Muara Jalai of the measurement results obtained 392.609 Ha. To discharge the mainstay calculate using methods Mock gained 0.06 m3/ sec. In this study used a variation cropping paddy-rice-pulses and rice-crops-crops at planting time in August, September. The research result shows that the most optimal to meet the criteria for each period is the cropping pattern of rice-paddy-planting crops with September.Keywords: Optimization of irrigation Muara Jalai using Mock.